NAVIGATING THE CHALLENGES OF LEGAL ENGLISH LEARNING: THE ROLE OF VOCABULARY AND MOTIVATION FOR LAW STUDENTS - Sunandar, Sunandar; Roni, Roni; Andang, Baharuddin (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study explores the challenges faced by law students in Sidrap Regency when learning Legal English, with a specific focus on the roles of vocabulary acquisition and student motivation. Legal English, as a specialized form of language used in the legal profession, poses unique learning challenges, particularly in terms of its complex terminology and concepts. The research highlights how a limited vocabulary can hinder students' understanding and application of legal texts, while also examining the impact of motivation on the learning process. Through a mixed-methods approach, the study gathers data from both surveys and interviews with law students in Sidrap Regency, aiming to uncover the strategies employed to overcome these obstacles and the factors that influence their motivation. The findings suggest that while vocabulary expansion is crucial, fostering intrinsic motivation through relevant teaching methods and a supportive learning environment can significantly enhance students' engagement and proficiency in Legal English. This research contributes to the understanding of effective pedagogical approaches in teaching Legal English to law students in regional contexts